Sustainable farming genes: spatial distribution and influencing factors of Chinese Agricultural Heritage Sites (CAHSs) - Li, Chang; Tong, Tong; Huang, Xiaohui (Frontiers in Sustainable Food Systems, 2023)
Agricultural heritage is a fundamental aspect of cultural heritage, as it is of significant cultural, economic, and biological value. The objective of this study is to reveal the spatial distribution and change of the Chinese Agricultural Heritage Site (CAHS) by means of spatial analysis. The results show that: (1) The distribution of 532 CAHSs (7 types) is patchy, and the horticulture system is gaining the quantitative advantage (55.26%), (2) The distribution of CAHSs shows the spatial aggregation of “dense in the east and sparse in the west.” The areas of Beijing, Shandong, Zhejiang, and their surroundings form the densest belt region of the heritages, and 44.17% of the CAHSs are distributed in this belt, (3) Single factor analysis shows that culture, population, soil, and elevation are the most critical driving forces that influence the distribution (all explanatory power > 0.20). Two factors interaction analysis confirms that the distribution is influenced by the enhancement of both natural and human factors. Of these, a high explanatory power (>0.70) is related to the matching between culture factors, population factors, and geographic factors (i.e., elevation, soil, and river). This study has the potential to provide scientific evidence for CAHS assessment, protection, and sustainable development.